The Long Twilight of Gold: How a Pivotal Practice Persisted in the Assemblage of Money. (2022) - Jabko, Nicolas; Schmidt, Sebastian
Abstract: Why has gold persisted as a significant reserve asset despite momentous changes in international monetary relations since the collapse of the classical gold standard? IPE theories have little to say about this question. Conventional accounts of international monetary relations depict a succession of discrete monetary regimes characterized by specific power structures or dominant ideas. To explain the continuous importance of gold, we draw on insights from social psychology and new materialist theories. We argue that international monetary relations should be understood as a complex assemblage of material artifacts, institutions, ideas, and practices. For much of its history, this assemblage revolved around the pivotal practice of referencing money to gold. The centrality of gold as experienced by policymakers had important effects. Using archival and other evidence, we document these effects from the 1944 Bretton Woods conference through the transition to floating exchange rates in the mid-1970s; most IPE scholars underestimate the role of gold during this period. Power relations and economic ideas were obviously important, but they contributed little to a fundamental development: the long process of reluctantly coming to terms with the limitations of specie-backed currency, and the progressive and still ongoing decentering of gold in international monetary relations.